Pengaruh Pengetahuan, Reputasi, Religiusitas, dan Motivasi terhadap Minat Menabung pada PT Bank Syariah Indonesia KCP Bung Tomo: (Studi pada Masyarakat Kelurahan Sungai Keledang) - Aris Tri Cahyono; Dina Rahmawanti (Jurnal EKSIS, 2022)
This study uses quantitative methods. The data collection technique in this study used a questionnaire distribution technique. The sample in this study were 114 respondents. Data analysis techniques that will be used in this study are Validity Test, Reliability Test, Multiple Linear Regression Test, t Test, f Test, Correlation Coefficient, Coefficient of Determination and using IBM SPSS Version 23 software. The results of this study partially knowledge variables have a significant effect on interest in saving at PT Bank Syariah Indonesia KCP Bung Tomo, seen from Tcount > Ttable (2.812 > 1.981) and sig value of 0.006 <0.05, partially reputation variable has no significant effect on interest in saving at PT Bank Syariah Indonesia KCP Bung Tomo , seen from Tcount < T table (1,249 < 1,981) and sig value of 0,214 > 0,05, partially religiosity variable has no significant effect on interest in saving at PT Bank Syariah Indonesia KCP Bung Tomo, seen from Tcount < T table (1,279 < 1,981) and the sig value of 0.204 > 0.05, partially the motivation variable has a significant effect on the interest in saving at PT Bank Syariah Indonesia onesia KCP Bung Tomo, seen from Tcount > T table (2,423 > 1,981) and sig value of 0.017 < 0.05, simultaneously the variables of knowledge, reputation, religiosity and motivation affect interest in saving at PT Bank Syariah Indonesia KCP Bung Tomo, seen from Fcount > Ftable (10,955 > 2,45) and the sig value is 0.000 < 0.05.